Analisis Pengaruh Model Project Based Learning dan Sikap Ilmiah Terhadap Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Lubis, Havifah; Suyanti, Retno Dwi; Lubis, Wildansyah (Jurnal Paedagogy, 2022)
This study aims to analyze students’ creative thinking skills and scientific attitudes taught by the project-based learning model and guided by ordinary learning. This study used a quasi-experimental method. The population in this study were all fifth-grade students of State Elementary School 132415 Tanjungbalai City for the 2021/2022 Academic Year. The samples were taken in class V A and class V B. The instruments of this research were the science process ability test, creative thinking ability test, and scientific attitude instrument. The data obtained were analyzed using two-way ANOVA. The study showed that the creative thinking ability of students who are taught by project-based learning was better than students who were led by ordinary learning (sig. = 0.000 < 0.005). Moreover, the creative thinking ability of students with a high scientific attitude was better than those with a low scientific attitude. There is an interaction between the two learning models with scientific attitudes influencing creative thinking skills and the most developed creative thinking skills, namely aspects of fluent thinking skills.